Optimization of fermentation process of mulberry-grape compound fruit wine by response surface methodology - ZHANG Yao, TANG Fengxian, SHAN Chunhui, ZHAO Xinxin, ZHAO Shimin, CHEN Xinjun (Zhongguo niangzao)
Mulberry-grape compound wine was prepared by fermentation with mulberry as main raw material. The fermentation process was optimized by single factor experiments and response surface experiments using sensory scores and alcohol content as evaluation indexes, and the physicochemical indexes and antioxidant activities were determined before and after fermentation. The results showed that the most suitable grape variety for mixed fermentation with mulberry was muscat grape, and the optimal fermentation process conditions were as follows: mass ratio of mulberry juice and muscat grape 9∶1, fermentation temperature 20 ℃, initial pH value 4.4, and initial sugar content 22 °Bx. Under these optimal conditions, the alcohol content and sensory score of mulberry-grape compound wine were 7.86%vol and 87.3 points. After fermentation for 60 h, total sugar and pH decreased from 219.60 g/L and 4.40 to 60.70 g/L and 4.26, respectively. The scavenging rates of DPPH and OH free radical increased by 12.32% and 24.03%, respectively. The contents of total acids, total phenolics and total flavonoids increased by 1.77 g/L, 159.67 mg/L and 34.46 mg/L, respectively.